Physicochemical and biological compatibility of insecticide mixtures with acaricide in the management of Brevipalpus yothersi - Della Vechia, Jaqueline F. [UNESP]; Bassanezi, Renato B.; Andrade, Daniel J. [UNESP] (Systematic and Applied Acarology Society, 2019)
Citrus leprosis, caused by Citrus leprosis virus cytoplasmic type (CiLV-C), is one of the major citrus diseases. Such disease is mainly managed by controlling the vector, which is a mite of the genus Brevipalpus (Acari: Tenuipalpidae). To increase pest control spectrum and reduce costs, citrus growers often prefer to tank mix pesticides. However, the effect of pesticide combinations made up of insecticides and acaricides is little known yet. Therefore, our goal was to evaluate the physicochemical compatibility of spray mixtures with acaricides (spirodiclofen, propargite, and cyflumetofen) and the most commonly used insecticides in citrus orchards, as well as to evaluate their biological effect on Brevipalpus yothersi (Baker). Mixing insecticides with the acaricides such as spirodiclofen, propargite, and cyflumetofen had no interfere with the physicochemical stability of tank mixtures. However, the combination of imidacloprid, bifenthrin, cypermethrin, and phosmet with spirodiclofen reduced acaricide control efficiency in 20.9%, 18.9%, 9.7%, and 21.9%, respectively. These mixtures are not recommended for B. yothersi control.
Keywords: antagonism; citrus leprosis mite; Diaphorina citri; incompatibility; interaction; tank mixture